A numerical model for the tidal oscillation and current in the Gulf of Tonkin - Ngoc Duyet, Tran Thi; Ninh, Pham Van; Quynh, Do Ngoc (Vietnam Journal of Mechanics, 2001)
in this paper results of a numerical model, based on the TIDEFLOW-2DSoftware, for the tidal oscillation and current in the Gulf of Tonkin (GT) are presented. The model was tested as follows: i) the observed values of the four main tidal constituents M2, S2, K1, 01 at the 44 coastal stations and islands were compared with computed ones; ii). the computed tidal levels were compared with the correlative ones in the Tide Tables at the six stations: Hon Gai, Cua Ong, Hon Dau, Cua Hoi, Cua Gianh and Cua Tung in many monthly periods; iii) the results of computed tidal levels and currents were compared with the observed data. The results of testing show a good agreement between the available data and computed values, therefore we can use this model for simulation t ide level and current of GT. The results of using this model in GT: distribution of the major harmonic constituents; the tidal elevation and current patterns; the extremal values of the tidal level and current,... will be published later.